Morfologia comparada da genitália feminina de Mantodea (Dictyoptera) - Maldaner, Caroline (Entomologia, 2022)
In the females of Mantodea the abdominal segments VII, VIII, and IX are morphologically modified to perform genital functions, therefore named genital segments. Historically in Mantodea studies, the abdominal morphology and the female genitalia have been barely explored. Hereupon, morphological and comparative studies of the female genitalia in Mantodea provide grounds for a new group of characters that may help clarifying the relations between taxonomically unstable groups. Besides, morphological works make it possible to include data about the ovipositor in phylogenetic studies, so far never explored in the order, and fulfill the lack of knowledge about the female genitalia morphology. Thus, the goals of this study were: to analyse, describe and illustrate in detail the female genital morphology of different genera of Mantodea; to compare the analysed females based on the morphology found; and to morphologically analyse, describe, illustrate and discuss the gland of ventral fold, spermatheca, and lateroepigynal pouch, which integrate the female genitalia. For that, the thesis was splitted into three chapters: I) the female genitalia morphology of Oxyopsis was described and illustrated in detail. In addition, a comparative analysis to Sphodromantis was provided. II) a comparative study of the female genitalia of Acanthops; Coptopteryx; Creobroter; Geomantis; Liturgusa; Mantis; Musoniella; Oxyopsis; Phyllocrania; Pseudocreobotra; Sibylla and Sphodromantis was presented, showing detailed illustrations and descriptions. III) a comparative morphological study was done based on optical and scanning electron microscopy of the spermatheca, lateroepigynal pouch, and gland of ventral fold of Oxyopsis; Sphodromantis e Coptopteryx. The results generated a set of formerly unknown information about the order and provided solid grounds for future works about the female genitalia in Mantodea, with the hope that such conclusions stimulate and facilitate the morphological study of the female genitalia as well as the feature of female characters in phylogenetic studies and in the taxonomy of Mantodea.
Keywords: Morfologia; Mantodea